Strategic Planning and Management of Educational Human Resources at Elementary School - Annisa Judithya A.N.A; Fery Diantoro (International Journal of Management, Innovation, and Education, 2024)
Human resource planning in educational institutions serves as a fundamental pillar of strategic management that directly affects institutional performance, teacher effectiveness, and educational quality. In response to increasing demands for accountability and competitiveness, this study examines the strategic human resource planning and management practices at SDIT Al-Mawaddah, an Islamic-based elementary school that integrates religious and academic excellence. The research aims to analyze the implementation of HR strategies in optimizing recruitment, placement, and development of teachers and staff while ensuring alignment with the school’s vision, values, and national standards. Employing a qualitative descriptive method, data were collected through interviews, documentation, and observation, and analyzed using thematic analysis to explore stages of HR planning including needs assessment, recruitment, selection, training, and evaluation. Findings indicate that SDIT Al-Mawaddah applies a structured planning process encompassing workload analysis, competency mapping, transparent recruitment, and continuous professional development grounded in Islamic principles. Challenges identified include staff retention and balancing academic and religious qualifications. The study concludes that strategic HR planning has enhanced institutional performance and educational service quality, highlighting the importance of sustaining professional growth, career development, and adaptive management integrated with Islamic educational values to ensure a sustainable and high-performing school organization